Cochlear Trajectory in Pediatric Patients. (23rd August 2013) - Jackson, Neal; Givens, Victoria; Carpenter, Clelie; Hurth, Charles; Arriaga, Moises; Ying, Yu‐Lan Mary; Jeyakumar, Anita S.
Abstract : Objectives: 1) Study pediatric temporal bone anatomy using high resolution temporal bone imaging. 2) Analyze the anatomical differences in infant (< 2 years old) versus toddler (2‐5 years old) versus child (6‐10 years old) versus preadolescent and adolescent (>10 years old) as it pertains to cochlear implantation Methods: A retrospective chart and radiologic review was done of pediatric patients at our institution undergoing high resolution computed tomography (CT) scan of the temporal bones from April 2001 to February 2013. Charts were reviewed for clinical and demographic information. Scans were reviewed by experienced surgeons, radiologists, or both to study the Cobb angle between an ideal trajectory of a cochlear implant into the basal turn of the cochlea and a realistic approach for surgical insertion. Results: Seven hundred fifty patients were identified. Seven hundred and twenty‐three charts and scans (1446 ears) were reviewed, and 27 patients were eliminated due to poor scan quality. The age range was 8 days to 22 years. Fifty‐six point three percent (n = 407) of patients were male. Each group of patients was evaluated. One hundred and five patients were < 2 years old, with Cobb's angle ranging 22.3‐36.4°. One hundred and forty‐seven patients were 2‐5 years old, with Cobb's angle ranging 14.6‐31.7°. Two hundred four patients were 6‐10 years old, with Cobb's angle ranging 7.7‐22.3°. Two hundred and fifty‐seven patients were >10 years old, with Cobb's angle ranging 7.7‐27.2°. Conclusions: Despite considerable variations, there is a substantial difference in the Cobb's angle among the age groups. The largest difference is between infancy (< 2 years old) and toddler (2‐5 years old). These differences are surgically relevant for round window identification and facial nerve safety during cochlear implant surgery in infants.